Multifunctional Polymeric Biodegradable and Biocompatible Coatings Based on Silver Nanoparticles: A Comparative In Vitro Study on Their Cytotoxicity towards Cancer and Normal Cell Lines of Cytostatic Drugs versus Essential-Oil-Loaded Nanoparticles and on Their Antimicrobial and Antibiofilm Activities - Rebecca Alexandra Puiu; Alexandra Cătălina Bîrcă; Valentina Grumezescu; Liviu Duta; Ovidiu Cristian Oprea; Alina Maria Holban; Ariana Hudiță; Bianca Gălățeanu; Paul Cătălin Balaure; Alexandru Mihai Grumezescu; Ecaterina Andronescu (Pharmaceutics, 2023)
We report on a comparative in vitro study of selective cytotoxicity against MCF7 tumor cells and normal VERO cells tested on silver-based nanocoatings synthesized by the matrix-assisted pulsed laser evaporation (MAPLE) technique. Silver nanoparticles (AgNPs) were loaded with five representative cytostatic drugs (i.e., doxorubicin, fludarabine, paclitaxel, gemcitabine, and carboplatin) and with five essential oils (EOs) (i.e., oregano, rosemary, ginger, basil, and thyme). The as-obtained coatings were characterized by X-ray diffraction, thermogravimetry coupled with differential scanning calorimetry, Fourier-transform IR spectroscopy, IR mapping, and scanning electron microscopy. A screening of the impact of the prepared nanocoatings on the MCF7 tumor and normal VERO cell lines was achieved by means of cell viability MTT and cytotoxicity LDH assays. While all nanocoatings loaded with antitumor drugs exhibited powerful cytotoxic activity against both the tumor and the normal cells, those embedded with AgNPs loaded with rosemary and thyme EOs showed remarkable and statistically significant selective cytotoxicity against the tested cancercells. The EO-loaded nanocoatings were tested for antimicrobial and antibiofilm activity against Staphylococcus aureus, Escherichia coli, and Candida albicans. For all studied pathogens, the cell viability, assessed by counting the colony-forming units after 2 and 24 h, was significantly decreased by all EO-based nanocoatings, while the best antibiofilm activity was evidenced by the nanocoatings containing ginger and thyme EOs.